High-dose bolus tirofiban versus low-dose bolus in patients with acute coronary syndrome undergoing percutaneous coronary intervention - Taner Ulus; Utku Şenol; Senan Tahmazov; Kemal Iskenderov; Fezan Mutlu; Yüksel Çavuşoğlu (KARE Publishing, 2017)
Objective: Aim of the present study was to determine effects of high-dose versus low-dose intravenous (IV) bolus tirofiban on angiographic measures, ST resolution, enzymatic infarct size, and clinical outcomes in patients with acute coronary syndrome (ACS) who were undergoing percutaneous coronary intervention (PCI) and received current pharmacoinvasive therapy. Methods: Acute coronary syndrome patients (n=271, 85.6% male; mean age: 57.9+-12.6 years) from between 2009 and 2015 who received IV tirofiban therapy following PCI were retrospectively analyzed. All patients had received maintenance tirofiban infusion (0.15 μg/kg/min) after bolus dose and 600 mg clopidogrel. Percentage of patients undergoing drug eluting stent implantation procedure was 33.5%. Tirofiban was administered to all patients in bailout situation or for thrombotic complication after PCI.  Results: High-dose IV bolus group (25 μg/kg; n=140) was associated with greater ST segment resolution (66% vs. 50%, p=0.013) and reduced peak troponin release [12.4 ng/dL (range: 6.5-21.5 ng/dL) vs. 16.4 ng/dL (range: 10.1-27.4 ng/dL), p=0.001] compared with low-dose bolus group (10 μg/kg, n=131). Cardiovascular event rates were similar between groups at in-hospital, 1-month, and 6-month follow-up (p=1.000, 1.000, and 0.287, respectively). Percentage of patients with post-procedural Thrombolysis in Myocardial Infarction (TIMI) grade III flow, major, and minor bleeding were similar (p=0.085, 1.000, and 0.965, respectively).  Conclusion: Use of high-dose IV bolus tirofiban in addition to aspirin and high-dose clopidogrel improves ST segment resolution, reduces infarct size, and does not increase bleeding events in patients with ACS undergoing PCI compared with low-dose bolus. Angiographic measures and clinical endpoints were similar between groups.